Using the Fourier Transform in the Analysis of Vibration Load Tests of Heterogeneous Mechanical Systems - Bittner, Václav; Tuček, Richard; Panská, Šárka; Svoboda, Martin; Jelen, Karel (Manufacturing Technology Journal, 2017)
The aim of this study was to find possibilities of using the Fourier transform in the analysis of vibration load tests of heterogeneous mechanical systems, especially those of a biological nature. The study applied the idea that the dispersion of a stationary stochastic signal depends on its power spectral density. We have verified that a sophisticated reduction in the spectral power of the ergodic signal may be used to filter it effectively. The proposed procedure is suitable for the detection and separation of harmonic artefacts. We have created an algorithm in the MATLAB environment and tested its functionality when analysing the vibration transfer within the human axial system.
Keywords: Signal Filtering; Vibration Analysis; Heterogeneous Systems; Fourier Transform